Digitalisasi Pembelajaran IPAS melalui Pengembangan Bahan Ajar KARSA-NUSA Berdiferensiasi untuk Meningkatkan Kemampuan Berpikir Kritis - Aprianis Eka Pratiwi; Hari Subiyantoro; Imam Sujono (Universitas KH. Abdul Chalim Pacet Mojokerto, 2025)
Critical thinking is one of the key competencies in Natural and Social Sciences (IPAS) learning. However, observations indicate that this skill remains low among fifth-grade students at SD Negeri Soko, Tulungagung Regency. One contributing factor is the lack of learning materials that accommodate students’ diverse needs, interests, and readiness levels. This study aims to develop Karsa-Nusa digital learning materials based on differentiated instruction to enhance students’ critical thinking skills. The research employed a research and development (R&D) method using a modified Borg and Gall model consisting of ten stages, from preliminary study to product dissemination, with 30 students as field trial subjects. The instruments included validation sheets, response questionnaires, and pretest–posttest questions. Validation results indicated that the materials were highly valid, with scores of 72.5/80 from material experts and 60.5/72 from media experts, exceeding the minimum eligibility threshold of 85%. Field trials showed positive student responses regarding usability and design. The t-test revealed a significance value of 0.000 < 0.05, with average scores increasing from 67.883 to 87.167 and an N-Gain of 0.601 (medium–high category). Thus, the Karsa-Nusa digital learning materials are valid, practical, and effective in improving students’ critical thinking skills in IPAS learning.